Effect of intermaxillary tooth-size discrepancy on accuracy of prediction equations for mixed dentition space analysis for Davangere population - Siddhi Samir Tejani; Poornima Parameswarappa; K Mallikarjuna; N B Nagaveni; K B Roopa; Neena I Eregowda (Wolters Kluwer Medknow Publications, 2022)
Context: In the mixed dentition period, malocclusion is in dormant stage, any interception should be preceded by a mixed dentition space analysis. Aims: To derive new regression equation in sample subjects (indigenous group) with no intermaxillary tooth size discrepancy (Bolton's ratio) residing in Davangere and to evaluate its accuracy. To assess the difference of tooth dimensions between males and females and difference between right and left of dental arches. Setting and Design: Descriptive study. Subjects and Methods: One hundred and fifty children (11-15 years) were included and dental casts were made. A digital Vernier caliper was used for the measurement of teeth. Bolton's ratio was calculated. Group A: Casts without Bolton's discrepancy and Group B: Casts with Bolton's discrepancy. Statistical Analysis Used: The data were analyzed with the SPSS software version 22.0. New regression equations were derived using correlation and regression analysis. Results: No statistically significant difference was recorded between the actual and predicted mesiodistal widths (MDWs) of permanent canine and premolars in maxilla and mandible, with/without Bolton's discrepancy. Males had statistically significant higher mean in maxillary and mandibular canine dimensions than female and no statistically significant difference between right and left side of dental arches was found. Conclusion: New regression equation was formulated for Davangere population, in which actual and predicted widths of permanent canines and premolars were found to be almost similar when established from sample with/without Bolton's discrepancy. In MDWs, the canine showed significant sexual dimorphism and no clinically significant variations were seen in the right and left sides of both the arches.